1985
DOI: 10.1042/bj2300517
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of caeruloplasmin in stored human extracellular fluids in relation to ferroxidase II activity, lipid peroxidation and phenanthroline-detectable copper

Abstract: No Cu(II) ion is measurable in human serum or synovial fluid by the phenanthroline assay. On storage of human serum or synovial fluid at 4 degrees C, phenanthroline-detectable copper appears, lipid peroxidation occurs, ferroxidase I activity declines and ferroxidase II activity rises, yet there is no fall in immunologically detectable caeruloplasmin. Storage of body fluids at -20 degrees C or -70 degrees C slows, but does not prevent, these deteriorative changes. It is suggested that the presence of low-molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 27 publications
(34 reference statements)
1
41
2
Order By: Relevance
“…CP also has antioxidant properties (Gutteridge et al 1985). It has been reported that ROS inhibit CP activity (Gutteridge et al 1985). The decrease in CP activity along with other antioxidants in BD group may support this claim and it seems to be an expected result.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…CP also has antioxidant properties (Gutteridge et al 1985). It has been reported that ROS inhibit CP activity (Gutteridge et al 1985). The decrease in CP activity along with other antioxidants in BD group may support this claim and it seems to be an expected result.…”
Section: Discussionmentioning
confidence: 80%
“…The decrease in CP activity along with other antioxidants in BD group may support this claim and it seems to be an expected result. However, it is also possible that increased oxidants may be responsible for the decrease in CP activity, as stated (Gutteridge et al 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pooled gruel from several lesions in the same aorta was frozen at -70°C. Storage at -70°C did not exceed 1 month which, normally does not result in oxidative deterioration of biological samples [21].…”
Section: Gruel Extractionmentioning
confidence: 99%